2015
DOI: 10.1002/lary.25424
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the prevalence of and factors associated with laryngeal diseases among the general population

Abstract: 2b.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 38 publications
(63 reference statements)
2
45
0
Order By: Relevance
“…The findings correlate with the data in general population (23). Also, according to the data found by previous studies, voice problems are more frequent in women (4,12,21) because they have shorter vocal folds that produce higher fundamental frequency and because of smaller quantity of vocal folds hyaluronic acid that is essential for wound repair (25).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The findings correlate with the data in general population (23). Also, according to the data found by previous studies, voice problems are more frequent in women (4,12,21) because they have shorter vocal folds that produce higher fundamental frequency and because of smaller quantity of vocal folds hyaluronic acid that is essential for wound repair (25).…”
Section: Discussionsupporting
confidence: 86%
“…Previous reports have shown the presence of vocal nodules in 16.9% of teachers and 4.34% in control group; vocal polyp was revealed in 2.4% of teachers (22). In the general population study occurrence of vocal nodules was 1.5% and vocal polyp 0.4% (23). Reported rates are probably different because of different study population and methodological approach.…”
Section: Discussionmentioning
confidence: 83%
“…2023 To measure physical activity, the participants were asked about the number of days they engaged in vigorous exercise with considerable shortness of breath for >10 minutes in the last week and the number of days they engaged in moderate exercise with slight shortness of breath for >10 minutes in the last week. 21 Monthly income was separated into lowest, low-middle, upper-middle, and highest quartiles, 2023 based on methods recommended by the Organization for Economic Cooperation and Development 24 (dividing household income by the square root of the number of household members). To explore the influence of the education level, the “low” education group was defined as uneducated participants and those who had graduated only from elementary or middle schools, whereas high school comprised the “middle” group, and junior college graduates, graduate school, and college graduates were assigned to the “high” group.…”
Section: Surveymentioning
confidence: 99%
“…21 Alcohol consumption was divided into 4 groups: none, ≤1 time a month, 2 to 4 times a month, and ≥2 times a week. 20,21 Smoking status was classified as nonsmoker, past smoker, and current smoker. 21 Past smokers who had quit smoking <1 year previously were considered as the current smoker group.…”
Section: Surveymentioning
confidence: 99%
“…To date, numerous epidemiological studies have confirmed that subjective voice disorders are an independent risk factor of dysphonia [16]. However, it has not yet been verified as a risk factor in Korean adults.…”
Section: Introductionmentioning
confidence: 99%